Perception of tourism vocational high school teachers in the learning environment survey on the implementation of national assessment in 2021 - Rahmadan Rahmadan; Syukri Hamzah (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2021)
This article describes the perception of tourism Vocational High School Teachers in Bengkulu City, Bengkulu Province in the Learning Environment Survey on the implementation of the 2021 National Assessment. The purpose of this study is to describethe level of teacher preparation and the level of teacher implementation implementation in the Learning Environment Survey activities in schools; alsodescribing the impression and/or message, supporting factors and inhibiting factors; and solutions or efforts to overcome the inhibiting factors of the Learning Environment Survey activities in schools in the 2021 National Assessment activities. This research is a Qualitative Descriptive Study on Tourism-based Vocational High School Teachers in Bengkulu City, Bengkulu Province.In this research, the researcher use Miles and Huberman’s theory in analyzing the dataconsists of three concurrent flows of activity: data reduction, data display, and conclusion drawing/verification. Based on the results of the study, it can be concluded that the perception of tourism-based Vocational High School Teachers in the Learning Environment Survey on the implementation of Assessment National in 2021 is really positive and hopes that the implementation of the Learning Environment Survey next year can run even better along with the improvement in the quality of the learning climate in an effort to create a conducive learning system and atmosphere in schools so that it has a very good and significant impact in achieving improvement. student achievement and learning outcomes.